(untitled) (The Research of Medical Science Review, 2025)
Introduction: Cardiovascular disease (CVD) constitutes a significant public health problem worldwide accounting for 35% of global deaths. TIMI score is a rapid, effective tool for stratifying risk in ST elevation myocardial infarction (STEMI) patients who receive fibrinolytic therapy. It is a convenient bedside method used for predicting 30-day mortality in these patients. However, the data on the validation of TIMI score is scarce in STEMI patients who do not undergo any reperfusion therapy or primary PCI. This study was designed to evaluate the efficacy and prognostic performance of TIMI score in STEMI patients to determine the optimal revascularization strategy. The study also determined the association of TIMI score with the in-hospital mortality. This will help in improved patient care and selection of better treatment options for these patients. Methodology: It was a prospective, cross-sectional study conducted at the Emergency Department of Rawalpindi Institute of Cardiology, Rawalpindi from 01-07-2024 to 31-12-2024. The study was approved by the Ethical Committee of the Hospital. Ninety four patients with the diagnosis of acute ST-segment elevation myocardial infarction were enrolled in the study by convenient sampling technique. The TIMI risk score was calculated for each patient. The patients were followed-up for 30 days mortality. The data was entered and analyzed using the Statistical Package for Social Sciences (SPSS) version 25. Results: The majority (24.5%) of the patients had a TIMI score of 2 followed by score 6(23.4%) and 3(14.9%). Mortality at 30 days occurred in 9(9.6%) out of 94 patients. Out of these 9 patients, 6 patients had a TIMI score of 6, 2 patients had a TIMI score of 4 and 1 patient had a TIMI score of 2. There was a significant association between the TIMI score and 30-days mortality with a pvalue of 0.03. Conclusion: TIMI score is a robust, effective tool for risk stratification in patients with STEMI who do not receive any reperfusion therapy or primary coronary revascularization. There is a positive correlation between higher TIMI risk score and in-hospital mortality among patients presenting with acute ST segment elevation myocardial infarction.